Kultivasi Mikroalga Menggunakan Media Af6 Pada Berbagai PH - Jelizanur Jelizanur; Padil Padil; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Microalgae cultivation is one technique to grow microalgae in a controlled environment. Cultivation aims to provide a single species in microalgae mass culture for harvesting. This research used AF6 media with a volume of 90 ml and 10 ml of microalgae. The purpose of this research was to cultivate microalgae using AF6 media with variations in pH 4, 6, 8 and types of microalgae namely Chlamydomonnas sp (chl), Chlamydomonnas sp (019), Chlamydomonnas sp (4), Chlamydomonnas sp (5), Chlorella sp (6 ). The results showed that pH had a significant effect on microalgae cultivation. Microalgae Chlorella sp (6) with a combination of treatment pH 8 and observation time of the 10th day was the best treatment of all types of microalgae cultivated that is equal to 0.1255.Keywords: microalgae, AF6 media, pH